A Prototype of Salt Gradient Solar Pond as Alternative Energy Source for Coastal Communities in Bengkulu - Mainil, Afdhal Kuniawan (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
One of the developing technologies of renewable energy is the Salt Gradient Solar Pond (SGSP). SGSP utilize solar energy by storing its thermal energy in a pond of saline solution. Bengkulu Province has a high intensity of sunlight and a long coastline with an abundance of salt water. Therefore, it is a very suitable location for further development of SGSP technology. The design of SGSP prototype had been carried out by using a 1 m3 cylinder as the saline solution pond. The density and temperature of the solution were measured at 11 points from the bottom to the top of the cylinder. The results show that the keeper of the pond, the more density of the solution, in which the highest solution density was at the bottom of the pond, i.e., 1.206 gr/cm3. The average temperature of the solution was 44.2°C. The maximum temperature, which was 48.7 °C, was observed around the storage zone, about 0.3 m from the pond‘s bottom. The results of the measurements of salinity gradient and temperatures show that this prototype of SGSP is appropriate to be used for storing heat around the storage zone.